2012
DOI: 10.1111/j.1435-5957.2011.00374.x
|View full text |Cite
|
Sign up to set email alerts
|

Proximity, accessibility and choice: A matter of taste or condition?

Abstract: Drawing on a combination of register data and travel survey data, this research explores changes in the accessibility to different amenities for the Swedish population between 1995 and 2005, as well as the reasons behind the changes: redistribution of either amenities or the population. Overall, proximity has increased concerning most of the amenities during the period. However, despite decreasing ‘potential’ distances, actual travel distances are growing longer due to, for example, an increasing selectivity i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…Several studies have reported that commute length is a major consideration in home and work location choice (17,18). In addition, accessibility to shopping and retail destinations (18,19) as well as recreational opportunities, health care facilities, and open space (20) has been shown to be significant in residential location choice. Zondag and Pieters (21) have shown that households are less likely to move from high accessibility locations.…”
Section: Factors Affecting Residential Relocationmentioning
confidence: 99%
“…Several studies have reported that commute length is a major consideration in home and work location choice (17,18). In addition, accessibility to shopping and retail destinations (18,19) as well as recreational opportunities, health care facilities, and open space (20) has been shown to be significant in residential location choice. Zondag and Pieters (21) have shown that households are less likely to move from high accessibility locations.…”
Section: Factors Affecting Residential Relocationmentioning
confidence: 99%
“…Consequently, spatial access to services should be complemented by research on travel behaviour regarding socio‐economic background, age, gender, culture, traditions, etc. (see e.g., Haugen et al focusing on the temporal dimension or Rodriguez and Rogers ), on the qualitative features of services (e.g., capacity of the facility, opening hours, quality of service), and research aimed at the perception of an acceptable level of SGI accessibility (an overview of discourses of ‘access’ is provided by Cass et al ). In this respect, the results of the present study should serve as an initial framework for subsequent research.…”
Section: Discussionmentioning
confidence: 99%
“…Improvements in spatial modelling software and GIS technology are causing an influx of potential-based accessibility modelling related to market access and economic development (Vickerman et al 2010), labour productivity (Polyzos and Arambatzis 2006), planning (Geertman and Ritsema Van Eck 1995), and recreation (Weber and Sultana 2012). As an indicator for proximity, potential is often used to indicate centrality/isolation in research assessing, for example, health care access (Haynes et al 2003;Rosero-Bixby 2004), social well-being (Middleton et al 2003), distance-to-work (Shuttlesworth and Gould 2010), and access to services (Haugen et al 2012). Spatial land-use land-cover change and ecosystem impact research often considers population potential as an explanatory variable, particularly in relation to urban land cover and threats to the natural environment (Braimoh and Onishi 2007;Verburg et al 2004) The potential model has also been used in smart interpolation applications to estimate the gridded distribution of human population (Deichmann and Eklundh 1991;Sweitzer and Langaas 1995;Wang and Guldmann 1996).…”
Section: Population Potentialmentioning
confidence: 99%